Vera Rubin a life - Mitton, Jacqueline 1948-; Mitton, Simon 1946- (Belknap Press of Harvard University Press, 2021)
The lure of the stars -- An aspiring astronomer -- Cornell and the rotating universe -- Georgetown, Gamow and galaxies -- A professional astronomer at last -- The call of the dome -- The delight of discovery -- Adventures in Andromeda -- Bright light on dark matter -- The dynamic universe -- Speaking out for women -- Wonderful life
Includes bibliographical references and index
2102
Keywords: Rubin, Vera C. -- 1928-2016; Rubin, Vera C / 1928-2016; Astronomers / United States / Biography; Women astronomers / United States / Biography; Dark matter (Astronomy); Biografie